Is postoperative cognitive dysfunction a disease of microglial inflammatory memory? A state-transition model from metabolic stress to epigenetic lock-in - Wu, Xiangyu; He, Tingye; He, Fei; Liu, Li (Frontiers in Molecular Neuroscience, 2025)
Postoperative cognitive dysfunction (POCD) remains a significant challenge in perioperative medicine, especially among older adults. Despite its prevalence, existing models centered on transient neuroinflammation fail to explain why cognitive deficits often persist long after systemic immune responses resolve. This review proposes a new framework: POCD is driven not by ongoing inflammation, but by a stable shift in microglial identity. We describe a closed-loop “inflammatory memory circuit” in which mitochondrial dysfunction, chromatin remodeling, and persistent polarization co-evolve to lock microglia into a hypersensitive, neurotoxic state. Recent studies suggest that surgical trauma triggers mitochondrial damage and mtDNA release, initiating innate immune activation via the cGAS–STING and NLRP3 pathways. These events engage epigenetic machinery—including HDAC3, DNMT3a, and long non-coding RNAs like MEG3—which reinforce transcriptional programs that lower activation thresholds and amplify cytokine output. Sustained M1-like polarization further propagates this loop, driving neuronal injury even in the absence of continued systemic cues. We outline experimental strategies to validate this model, including time-resolved single-cell transcriptomics and chromatin accessibility profiling. Therapeutically, we highlight HDAC inhibitors, SIRT1 agonists, and lncRNA-targeted interventions as potential strategies to disrupt the circuit before state-locking occurs. By reframing POCD as a glial fate transition rather than a transient immune reaction, this model offers mechanistic clarity and opens a path toward time-sensitive, precision interventions.